Phytochemical Analysis of Purple Sweet Potatoes (Ipomoea batatas) Roots Extract From Lawang and Kawi Mountain Cultivar, East Java, Indonesia - Alam, Fajar Mustika; Kurnianingsih, Nia; Fatchiyah, Fatchiyah (The Journal of Experimental Life Science, 2022)
Indonesia has wide cultivation of purple sweet potatoes (PSP) commodities, particularly in East Java province. However, the difference of phytochemical profiles in PSP among geographical regions has not been fully explored. This study aimed to analyze the phytochemicals, anthocyanin, and antioxidant activity profiles from two different cultivars of PSP from Lawang and Kawi Mountain region, East Java, Indonesia. The acidified methanol extract was identified for a phytochemical compound using standard methods. Antioxidant activity was analyzed using a ferric reducing assay. Anthocyanins were screened using ultraviolet-visible spectroscopy and total calculation. Both extracts have positive values in their alkaloid, phenolic, flavonoid, glycoside, and tannin content. Antioxidant activity was high with IC50 value 2.5 and 2.3 µg. mL-1 for Lawang and Kawi Mountain, respectively. Each cultivar has a similar peak at 521 nm at pH 1 and 530 nm at pH 4.5. Total anthocyanin calculation was showed that Lawang has higher anthocyanin content than Kawi Mountain cultivar. We concluded that PSP from Lawang has better anthocyanin content than the Kawi Mountain cultivar. We proposed that PSP from the Lawang cultivar has the potential to be explored in further research and health-related product development.